AFRICAN UNION (AU) AND CONFLICT RESOLUTION IN AFRICA - Chinonye Nnenna Nwokoroeze (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
This study focused on the African Union and conflict resolution in Africa with particular reference to the Darfur conflict in Sudan. The Darfur conflict has become a global problem and a test-case for Africa Union’s capacity in dealing with intractable conflicts in Africa. Two research questions were posed, to wit, what factors account for the nature and pattern of AU response to conflicts in Africa particularly to the crisis in Darfur region of South Sudan? And what indigenous mechanisms of conflict resolution can the AU leverage on to respond to conflicts in Africa instead of relying on external forces? The objectives of the study include determining the factors that define the nature and pattern of the AU response; and determining what indigenous mechanisms the AU can rely on to solve conflict situations in the continent. The study is anchored on the social identity theory developed by Henri Tajfel. Two research hypotheses were posed. The study adopted the descriptive research design. It relied on secondary sources of data and data were collected from textbooks, journals, and the internet. We adopted content analysis as our method of analysis. Among the findings are that the AU response to the Darfur conflict has been greatly impacted by the differences between sub-Sahara and North African states, external pressures and the indictment of former President al-Bashir by the International Criminal Court greatly; and that the AU has the capacity and latitude to leverage on indigenous knowledge of African history to develop mechanisms of conflict resolution instead of relying on external prescriptions. It is this context that we recommended that the AU should be more assertive in its peacekeeping initiatives by critically reassessing its Afro-Arab relations and exploring ways of enhancing the partnerships. Secondly, it is recommended that the AU should consider the adoption of African traditional conflict resolution Mechanisms since the Western prescription, despite their laudable intentions have always resulted in conflict relapse.